Estimasi Hasil Tangkapan Rajungan Di Pesisir Laut Jawa (Studi Kasus Kampung Bahari Tambak Lorok Semarang) - Bambang Trihardiyanto, Anton Pramono; Riani, Etty; Susilo, Adhi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This article examines estimates of crab catches on the Java Sea coast, with a focus on the case study of Kampung Bahari Tambak Lorok in Semarang. The research methods used include field surveys, catch data analysis, and statistical approaches to obtain a comprehensive picture of crab production in the region. The research results showed a significant decline in crab catches during a certain period, which was caused by various factors including climate change, human activities, and marine ecosystem dynamics. This research also investigates the phenomenon of “Ghost Fishing”, where nets left in the sea continue to catch fish by accident. The results of the analysis reveal that “Ghost Fishing” makes a non-negligible contribution to the decline in crab catches in the study area. Based on data from the Ministry of Maritime Affairs and Fisheries (KKP) Semarang, it is recorded that crab catches have decreased by 30% in the last five years. The implications of this decline in catches are debated in the context of marine resource conservation and sustainability planning for the crab fishing industry in Indonesia. This research makes an important contribution to the understanding of crab catch dynamics and highlights the need for sustainable marine resource management measures to ensure the future sustainability of the fishing industry. Keywords: Crab, Ghost Fishing, Catch Results, Decline, Marine Resource Conservation, Sustainable Fisheries.